The morphology evolution and crystallization behavior of microinjection molded polyoxymethylene/molybdenum disulfide nanocomposite. Issue 12 (21st November 2016) - Yang, Sen; Chen, Yinghong; Yang, Chaonan; Ding, Weiwei
ABSTRACT: Microinjection molding was carried out on polyoxymethylene (POM)/molybdenum disulfide (MoS2 ) nanocomposite prepared by solid state shear milling (S 3 M) technology. The morphology evolution and crystallization behavior were then investigated under different conditions of mold temperature and injection speed. The comparison between the microinjection molded micropart with conventional injection molded macropart was also conducted. Results showed that the higher mold temperature could improve the filling property and replication quality. The MoS2 particles played a heterogeneous nucleation role and remarkably affected the crystallization process of POM. Meanwhile, the crystallization orientation and skin‐core structure induced by the shear stress presented the similar evolution tendency under different microinjection conditions. The multi‐melting behaviors of microparts occurring under different microinjection conditions were attributed to the formation of shish‐kebab structures. The increase of crystallinity and the reduction of mechanical property occurring in macropart are related to its crystallization morphology formed, which is different from that of micropart. The results of this work would lay a foundation for preparation of POM/MoS2 transmission microparts with good comprehensive performance. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44625. Abstract :